2014
DOI: 10.1002/chin.201436055
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Iron‐Catalyzed C(sp2)—H and C(sp3)—H Arylation by Triazole Assistance.

Abstract: This method utilizes a triazole‐derived auxiliary for the iron‐catalyzed activation of otherwise inert C(sp2)—H and C(sp3)—H bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…At finite doping, however, the presence of even weak interactions among the electrons is predicted by several studies to lead to new collective behavior. Of particular recent interest are interaction-driven instabilities towards unconventional superconductivity in doped honeycomb systems [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Some early studies concluded that superconductivity might not be stable with respect to charge or spin order for the basic Hubbard model on the honeycomb lattice [2,3], and a possible quantum liquid state has been suggested recently for the van Hove singularity (VHS) filling [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At finite doping, however, the presence of even weak interactions among the electrons is predicted by several studies to lead to new collective behavior. Of particular recent interest are interaction-driven instabilities towards unconventional superconductivity in doped honeycomb systems [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Some early studies concluded that superconductivity might not be stable with respect to charge or spin order for the basic Hubbard model on the honeycomb lattice [2,3], and a possible quantum liquid state has been suggested recently for the van Hove singularity (VHS) filling [18].…”
Section: Introductionmentioning
confidence: 99%
“…A possible p + ip pairing state was also reported at low filling from determinantal quantum Monte Carlo studies; however, the sign problem poses restrictions on the accessible system sizes, interaction strengths and temperature ranges. In addition, Grassmann tensor renormalization calculations have been performed [14,15], and in Ref. [14], a d + id state is reported for the t − J model, while for infinite local repulsion a p + ip superconducting state, coexisting with ferromagnetic order, has been proposed for the Hubbard model at low doping [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation